Analysis of mitochondrial DNA sequence and copy number variation across five high-altitude species and their low-altitude relatives. Issue 2 (3rd July 2018) - Liu, Rui; Jin, Long; Long, Keren; Tang, Qianzi; Ma, Jideng; Wang, Xun; Zhu, Li; Jiang, An'an; Tang, Guoqing; Jiang, Yanzhi; Li, Xuewei; Li, Mingzhou
Abstract: High-altitude inhospitable environments impose a formidable life challenge for the local animals. Training and exposure to high-altitude environments produce both distinct physiological and phenotypic characteristics. The mitochondrion, an organelle crucial for the energy production, plays an important role in hypoxia adaptation. In this study, we investigated the mitochondrial DNA (mtDNA) polymorphism and copy number variation between the population pairs from distinct altitudes across the multi-species. Higher mitochondrial DNA control region's genetic diversity is conspicuous in high-altitude animals versus low-altitude relatives. We also found an accordant decrease of mtDNA copy number in most of the tissues from high-altitude animals. Compared to mammals, chickens have significantly distinct mitogenomic characteristics, and more significant changes in the skeletal muscle mtDNA copy number between high- and low-altitude individuals. Our study catches a snapshot of the biological similarities and differences in the mitochondrial high-altitude acclimation across the species.